Notes on Clock and Watch Making; with Descriptions of several Antique Timekeepers deposited in the Museum (Proceedings of the Society of Antiquaries of Scotland, 1862)
An account of the history of timekeeping and watchmaking in Britain and Europe. The article ends with a list of watches donated to the Society by the author, including any information he has on their makers or owners. Meeting notes for 21 May, 1860 are appended.